Migrant architects of the NHS : South Asian doctors and the reinvention of British general practice (1940s-1980s) - Simpson, Julian M. (Social histories of medicine., 2018)
Migrant Architects is the first book to assess the impact of the migration of doctors from the Indian subcontinent on postwar development of British general practice and by extension the ways in which they influenced the development of the NHS.